Cloning, nucleotide sequencing and expression of the gene factor Xa inhibitor from salivary glands of the tick, Ornithodoros savignyi - Neitz, A.W.H. (Albert Walter Herman) (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1994.